2013
DOI: 10.3892/ijo.2013.1783
|View full text |Cite
|
Sign up to set email alerts
|

Potent growth-inhibitory effect of a dual cancer-specific oncolytic adenovirus expressing apoptin on prostate carcinoma

Abstract: Apoptin is a chicken anemia virus-derived, p53-independent, bcl-2-insensitive apoptotic protein with the ability to specifically induce apoptosis in various human tumor cells, but not in normal cells. To explore the use of apoptin in tumor gene therapy, we assessed a recombinant adenovirus expressing the apoptin protein (Ad-hTERTp-E1a-Apoptin) in order to determine its lethal and growth-inhibitory effects on PC-3 and RM-1 cells in vitro and its antitumor effect on solid tumors in vivo. 3-[4,5-dimethylthiazol-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…For the melanoma A375 and B16 cell lines, the infection with the adenoviruses expressing apoptin were observed predominantly in a late apoptotic stage. Also, Ad-VT conferred significant survival benefits in vivo (29)(30)(31)(32). The mice lungs infected with Ad-VT had minimal metastatic nodules; whereas, the lungs from control or treated groups had severe metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the melanoma A375 and B16 cell lines, the infection with the adenoviruses expressing apoptin were observed predominantly in a late apoptotic stage. Also, Ad-VT conferred significant survival benefits in vivo (29)(30)(31)(32). The mice lungs infected with Ad-VT had minimal metastatic nodules; whereas, the lungs from control or treated groups had severe metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…NCI-H226 cells (1 × 10 7 /100 µL) were injected into the right hind leg of nude mice. The xenograft models were infected with Ad-VT (1 × 10 9 plaque forming unit, PFU; biweekly) via intratumor injection and gemcitabine (30,60, and 120 mg/Kg; weekly) via intraperitoneal injection. The length and width of the xenograft tumors were weekly measured using a vernier caliper.…”
Section: Tumor Xenograft Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptin in a protein form with transduction tags as a fusion protein has also been tried. [179,180]. Another study that employed a conditionally replicating adenovirus carrying apoptin demonstrated an inhibitory effect on melanoma cells, and suppressed both subcutaneous primary tumor as well as lung metastatic tumors [181].…”
Section: Apoptinmentioning
confidence: 99%
“…This allows a specific induction of apoptosis in cancer cells. [47] This ability to kill only tumor cells has been reported in breast [48] , head and neck [49] , prostate [50,51] , lung cancer, osteosarcoma [50] , hepatocellular [52] and nasopharyngeal [53] carcinoma. A study analyzed the ability to induce apoptosis of five truncated apoptin proteins in human breast adenocarcinoma MCF-7 cells and human liver Chang cells as control.…”
Section: Introductionmentioning
confidence: 99%